Cells of matter and life – towards understanding the structuring of particles and plankton patchiness in the Arctic fjords - Trudnowska, Emilia; Dragańska-Deja, Katarzyna; Sagan, Sławomir; Błachowiak-Samołyk, Katarzyna (Frontiers in Marine Science, 2022)
As the environmental conditions are typically not homogenous, especially in coastal regions, they must provide a mosaic of distinct habitats that can be occupied by particles and plankton in a characteristic way. Here we analyze and map the spatio-temporal distribution patterns and the internal structure of 94 patches of various size fractions of particles and plankton studied by fine resolution measurements of two compatible laser counters performed in the upper epipelagial of two Arctic fjords over six summer seasons. Detected patches generally occupied only the minor part of the studied upper water column (on average 12%), and frequently occurred as multi-size-fraction forms. The observed concentrations within the patches were mostly 1.6 times higher than the background concentrations (max 4.1). The patches ranged in size horizontally from 1 to 92 km (median length 12 km) and vertically from 5 to 50 m (median 26 m). Because the designated patches varied in terms of their forms and internal structure, a novel approach to classify their shapes is proposed. Accordingly, seven types of patches were distinguished: Belt, Triangle, Diamond, Flare, Fingers, Flag, and Rosette. The particles and plankton exhibited all types of these distribution patterns, regardless of the size fraction and location. The observed steepening size spectra slopes over years implies that proliferating Atlantic water advection, triggering increasing role of the smallest size fractions, played the crucial role on compositional dynamics on temporal scale. The recurring high concentration patches of particles and plankton near glaciers suggest that their melting, together with biological production, were the strongest factors generating patchiness on the local scale. An observed under several occasions depth differentiation among size fractions building together vertically thin multi-size-fraction patches is an interesting feature for further studies. Even if distribution patterns of particles and plankton did not clearly reflect all patterns in the environmental water structuring, they happened to be strictly related to the presence of glacier runoff, eddy, sea mountain and hot spots of chlorophyll fluorescence.